The gap between legal protection, good intentions and political restrictions. Unaccompanied minors in Norway - Hilde Lidén; Elisabeth Gording Stang; Ketil Eide (Social Work and Society, 2017)
This article presents legal regulations, policy and practice, as well as qualitative research, on several aspects of the implementation of the rights and living conditions of unaccompanied asylum-seeking minors (UAM) in Norway. The total text of the United Nations (UN) Convention on the Rights of the Child (CRC) 1989 is incorporated into Norwegian legislation through the Human Rights Act (1999). The Convention's main principles have also found their way into the Norwegian Constitution in 2014. The Norwegian Immigration Act of 2008 includes several provisions and formulations strengthening the legal position and rights of asylum-seeking children compared with the former Immigration Act 1988. UAM have an adjusted application process and are entitled to support of a legal guardian throughout the application process. They are placed in care or reception centers when waiting to their case to be proceeded. If granted residence permit the minor are settled in a municipality, continuing their education. UAM then will access equal citizen rights. Increased demand for stricter immigration policy in recent years, though, has resulted in a series of changes and new restrictions in law and practice that, at several levels, challenge the intention behind the Immigration Act's legal safeguards for child refugees, as well as the implementation of the CRC provisions.